The Orthodox Charismatic Gift. Issue 1 (1st March 2022) - Tateo, Giuseppe
Abstract: Based on ethnographic research conducted in a number of Orthodox parishes in Bucharest, this article discusses different conceptions of har among Bucharest Orthodox believers, practitioners, and clerics. Har stands for 'grace', 'charisma' or 'gift' depending on the context. An ethnographically grounded analysis of this emic concept, I argue, is essential for two main reasons. First, understanding grace through gratuity allows us to grasp diverse forms of religious change, such as committed church attendance and the detachment from communal religious life, in contemporary Romania. Second, seeing through the looking glass of Orthodox practice allows for unexplored insights into the workings of charismatic authority. The article ends with a seeming paradox: grace is 'something extra', an addition which is best grasped apophatically, that is, through subtraction.